Chimpanzee Turning Behavior During Spatial Navigation in Virtual Environments - Sarah E. Koopman; Matthias Allritz; Emma S. McEwen; Francine L. Dolins; Karline R. L. Janmaat; Kenneth Schweller; Josep Call (Animal Behavior and Cognition)
Primate spatial navigation is difficult to study in the wild due to limited knowledge of explanatory variables, and in captivity due to limited physical space. Presenting tasks in computer-generated virtual environments (VE) can overcome these constraints, providing precise location and timing data in completely configurable environments of any size. Here, we used VE to closely examine turning, a fundamental navigational behavior, to better understand whether chimpanzees make the shortest turn (<180°) to targets outside their field of view (FOV). We also examined how this behavior changed with experience in VE. Chimpanzees completed a first-person virtual food collecting task on a touchscreen involving two virtual foods, both initially visible on the screen, which they could approach and “collect” to receive a real food reward. Due to the first-person viewpoint in the VE, as they approached one food, the other food disappeared from the FOV depicted on the screen. We found limited efficient turning to the second food during early experience with VE and more efficient turning during later experience with VE, suggesting that this behavior develops over time. Although for most chimpanzees, efficient turning was accompanied by biases in food side choice and turn direction, they nevertheless also turned efficiently even when they went against those biases. We found individual differences in food side choice and turn direction over time, indicating no consistent progression of these turning behaviors in VE across individuals, but some within-individual consistency across tasks. By closely studying primate navigation behavior in VE, we can better understand how they perceive these environments, informing the design of future VE-based studies.